(untitled) (Journal of the College of Basic Education, 2023)
The packing efficiency of 20 samples (P1-P20) of food packaged in flexible plastic bags available in the markets of Baghdad was determined in this study, the results indicated that there was no batch number in P2, P3, P4, P7, P9, P19 and P20 and it was not clear in P1. Also, it was note the difference in the validity period of the samples and the non-conformity of others to the validity period in the Iraqi standard specification No. 1847. (2012). as it was 6 month in P1 and P2, while it was 24 month in P5, 12 month in P18 and it was not clear in P7, but rather it was replaced by the phrase (valid for consumption for a period of five years from the date of production). The results of the welding examination showed the failure of P3, P4, P5, P15, P16 and P17, while the obtained values were 611, 428, 223, 515, 326, 187, 288 and 440 mbar for P8, P9, P10, P11, P12, P13, P18 and P20, respectively, while the coating thicknesses were 0.048, 0.096, 0.093, 0.069, 0.088, 0.106, 0.110, 0.487, 0.142, 0.135, 0.136, 0.059, 0.099, 0.113 and 0.081. and 0.083, 0.063, 0.083, 0.127, and 0.094 µm for P1, P2, P3, P4, P5, P6, P7, P8, P9, P10, P11, P12, P13, P14, P15, P16, P17, P18, P19 and P20, respectively